Improvement of the processing of initial and final conditions of particles undergoing DEP effects in homogenous suspension using MATLAB / Noor Hidayah Amir Hassan - Noor Hidayah, Amir Hassan (2012)
Cell separation and manipulation are currently becoming highly purposeful due to its function variation and becoming possible due to the availability of dielectrophoresis (DEP) method. Commonly used in cancer cell detection and drug screening assessment, DEP are able to manipulate polarisable particles with the application of non-uniform electric considering the fact that movement will be induced onto the polarisable particles when placed in the electric fields. The application of DEP are used to be restricted in research for academic prospects only, rather than in manufacturing applications due to the laborious and time-consuming processes involved, but recently with the existence of multi-channels microelectrode array, real-time assessment of cell populations are accredited since each electrodes were being energized individually with desired voltage, frequency and phase. The physiological characteristics of cell populations are being extracted from DEP spectrum which was obtained from image processing technique which previously involves histogram-based algorithm and CMIS method. The current research attempts to introduce new method of determining the distribution of cells to be even or not. This is crucial in multiple dot system but not so much important for single dot system. This is because the algorithm developed based on CMIS and histogram plots are already proven to be effective. The proposed method named average counts attempt to manipulate the average grey level values of each pixels and standard deviation plot obtained is used to draw the conclusions from the findings.